Facilitator’s scaffolding strategies in a design-based learning context / Yee Ling Lee and Meng Yew Tee - Yee, Ling Lee; Meng, Yew Tee (2021)
Design-based learning (DBL) is a pedagogy grounded in inquiry towards generating artefacts to solve a real-life issue through an iterative engineering design process. Completing a design task is challenging. Scaffolding is necessary for supporting student learning in a DBL context. However, a review of the literature revealed that there are still significant implementation issues related to scaffolding student learning in this context. The roles played by facilitators in scaffolding student learning in a DBL context are also under-researched. This study aimed to investigate facilitator’s scaffolding strategies which could be used to help students integrate knowledge in a DBL context. This study involved a class of 27 Form 1 students in a national school. The students learned how to integrate knowledge from Science, Technology, Engineering, Arts and Mathematics (STEAM) subjects to design and construct a water filter. They were scaffolded by the facilitator throughout the implementation of this design task. Video recordings, student interviews and researcher's notes were used for data collection. Several vignettes were presented to illustrate how these scaffolding strategies were used to help students integrate knowledge. The research findings showed that the facilitator used various types of scaffolding strategies to support student learning based on their emerging learning needs. The scaffolding strategies were categorised into six types in terms of cognitive, linguistic, metacognitive, motivational, social, and strategic scaffolding. This study highlighted how multiple facilitator's scaffolding strategies could work as a system to help students develop a coherent understanding of the design task. This study provides guidance for teachers in pre-designing scaffolding into their instructional practice. This study also opens new lines of research which establish connections between application of scaffolding knowledge integration and interdisplinary learning context.